2015
DOI: 10.1111/ijtd.12045
|View full text |Cite
|
Sign up to set email alerts
|

Rules of engagement: the joint influence of trainer expressiveness and trainee experiential learning style on engagement and training transfer

Abstract: We investigated the joint effect of trainer expressiveness and trainee experiential learning style on training transfer intentions. Extending prior research where trainer expressiveness has been established as a positive predictor of transfer, we show that trainer expressiveness is more impactful for trainees with high (vs. low) experiential learning styles. Based on our findings, trainees' experiential styles -also related to one's intuition -emerge as important enhancers of transfer intentions, and should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…At least four theoretical implications can be drawn from our study. First, while affective experiences during trainings have been widely neglected in training and transfer research (Aguinis & Kraiger, ; Gegenfurtner et al ., ) or treated as a control variable only (Rangel et al ., ), our study shows that positive affect matters within training and is related to participants’ motivation to transfer, which is important for successful transfer of training. Positive affect experienced within training is a relevant training‐related factor that should no longer be neglected within training and transfer research.…”
Section: Discussionmentioning
confidence: 99%
“…At least four theoretical implications can be drawn from our study. First, while affective experiences during trainings have been widely neglected in training and transfer research (Aguinis & Kraiger, ; Gegenfurtner et al ., ) or treated as a control variable only (Rangel et al ., ), our study shows that positive affect matters within training and is related to participants’ motivation to transfer, which is important for successful transfer of training. Positive affect experienced within training is a relevant training‐related factor that should no longer be neglected within training and transfer research.…”
Section: Discussionmentioning
confidence: 99%
“…For instant, intention construct in TBP, is missing in training transfer model. Indeed, Rangel et al (2015) confirmed that understanding intention to transfer is important for a comprehensive understanding of training transfer. Thus, a hybridized model will improve understanding of transfer behavior.…”
Section: Introductionmentioning
confidence: 61%
“…In psychology, the intention construct is recognized as a crucial agent in human behavior ( Ajzen, 1991). Similarly, in the training transfer domain, Rangel et al (2015) demonstrated that a proper understanding of intention is necessary for a comprehensive understanding of training transfer (trainee behavior at work). Intention to transfer is the first and most critical phase (as well as a precondition) for the transfer process (Al-Eisa et al, 2009;Foxon, 1994;Grohmann et al, 2014;Holton, 1996).…”
Section: Intention To Transfermentioning
confidence: 99%
“…This study assumes that as flex professionals, trainers prefer to autonomously implement their training modules and facilitation processes to achieve learning goals based on their trainees’ various needs (Mazmanian, Orlikowski, & Yates, 2013). There are multiple routes to achieving learning goals through content knowledge and delivery style in instructional design (Harris, Chung, Frye, & Chiaburu, 2014; Rangel et al, 2015). Trainers often need to create improvised facilitation activities during unscripted scenarios that arise while advising their trainees.…”
Section: Research Variables and Hypothesesmentioning
confidence: 99%